Tantangan Penegakan Hukum Terhadap Kejahatan Siber Pada Era Digital di Jawa Tengah - Al-Ulamai, Ulil Amri; Harahap, Rustam Dahar Karnadi Apollo; Maskur, Ali (Fakultas Hukum Universitas Islam Batik Surakarta, 2025)
The rapid development of information technology has increased the intensity of cybercrime, especially in Central Java, which has a large digital population. Crimes such as online fraud, the spread of hoaxes, and online gambling are becoming increasingly difficult to handle due to their anonymous and cross-border nature. This research aims to analyse the challenges of law enforcement against cybercrime, evaluate the strategies of law enforcement agencies, and highlight the potential of the community's role in prevention. Using a qualitative method with a descriptive-analytical approach, data were collected through interviews, observations, and documentation, and then analyzed thematically. The research results show three main findings: technical and institutional limitations in handling cybercrime, strategic steps taken by the Central Java Police Cyber Crime Directorate, and the low literacy and community involvement in prevention. This research emphasises that the effectiveness of law enforcement can be significantly enhanced by the synergy of regulations, technology, and community participation. The implication is that policies are needed to integrate community-based repressive and preventive approaches. Further research is recommended to explore more inclusive and locally based digital literacy strategies, underlining the importance of continuous learning and adaptation in combating cybercrime.